From Intimate Memory to Global History. The Interactive Web-Documentary Between Authentication Strategies and Feeling Rehabilitation - Greco, Cristina (E|C, 2020)
In accordance with past research on the construction of the effect of reality and truth in the contemporary graphic novel (Greco 2014), this contribution aims to propose a reflection on the writing modalities of the collective memory in the interactive web-documentary. In particular, the research proposes the analysis of two exceptional case studies: a) Génération 14. Mémoire intime de la Grande Guerre, an interactive documentary that works on the collaborative reconstruction of the memory, and, b) First World War. The Story of A Global Conflict, The Guardian’s interactive documentary, which works on historical discourse and on the knowledge that is already given. The first case retraces the individual memories, by the use of documents and testimonies, enabling the user to reconstruct his own story and to find out who, among his loved ones, experienced the Great War; the second one concerns the Great War collective events, which are told by ten historians, whose narrations are translated into ten different languages. These case studies show a high degree of ambiguity and the need to create a synthesis to face the new connections through which the memory interacts in the semantic and figurative universe of the conflict. These are texts that activate a re-elaboration of the relationship between History and testimony and pose questions about the results of such a complex textuality, product of the mixture of forms and genres, from the historical account to the testimony, and to the autobiographical reconstruction of remembrance.